THE INFLUENCE OF RELIGIOUS COPING AND SOCIAL SUPPORT ON THE PSYCHOLOGICAL WELL-BEING OF NUNS IN THE CONGREGATION OF THE MISSIONARIES OF THE HOLY SPIRIT, EAST FLORES PROVINCE (International Journal of Cultural and Social Science, 2026)
Nuns face various demands in religious life, and to cope with these pressures, they generally employ religious coping strategies. This study aims to examine the impact of religious adjustment and social support on the psychological well-being of nuns in the Congregation of the Missionaries of the Holy Spirit. This study employed a quantitative approach with a cross-sectional design. Data were collected using a short version of the Ryff Psychological Well-Being Scale, the Brief RCOPE, and the Multidimensional Scale of Perceived Social Support. Multiple linear regression was used to analyze the data. The results indicate that religious adjustment and social support simultaneously significantly influence psychological well-being, with relatively limited contributions. Partially, religious adjustment and social support positively and significantly influence psychological well-being, with social support having a stronger influence.